Proceedings of the 2011 iConference 2011
DOI: 10.1145/1940761.1940778
|View full text |Cite
|
Sign up to set email alerts
|

Finding social roles in Wikipedia

Abstract: Abstract:The concept of "social role" has long been used in social science describe the intersection of behavioral, meaningful, and structural attributes that emerge regularly in particular settings and institutions. We use structural signature methods to identify key roles in a large distributed collaboration system (Wikipedia) by examining the distribution of edits across types of pages and the structure of relationships between editors. We distinguish between technical editors, substantive experts, vandal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
147
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(156 citation statements)
references
References 26 publications
7
147
0
2
Order By: Relevance
“…A plausible explanation for such structures are generalist editors who perform basic tasks such as spelling, grammar, and hyperlink corrections to contributed content that may have also been reviewed by specialists. Such technical editors may even be edited by other technical editors, as the language and wording of an article becomes more defined, adding to the density of this structure This explanation is also compatible with past observations of Wikipedia editors [14].…”
Section: Facebooksupporting
confidence: 87%
See 2 more Smart Citations
“…A plausible explanation for such structures are generalist editors who perform basic tasks such as spelling, grammar, and hyperlink corrections to contributed content that may have also been reviewed by specialists. Such technical editors may even be edited by other technical editors, as the language and wording of an article becomes more defined, adding to the density of this structure This explanation is also compatible with past observations of Wikipedia editors [14].…”
Section: Facebooksupporting
confidence: 87%
“…Such behaviors may emerge when two domain-specific specialists are only editing articles that only fall under their purview. This hypothesis is substantiated by previous research that found users labeled as substantive experts on Wikipedia exhibiting a similar ego-network structure [14]. Yet we still see a small amount of overlap between these two contributors, which may be done when editing Wikipedia articles that discuss many different topics.…”
Section: Facebooksupporting
confidence: 85%
See 1 more Smart Citation
“…For example, the structure of interactions in the user talk page network helped to distinguish between substantive experts and technical editors [15]. Moreover, preexisting social capital, operationalized as the proportion of collaborators being members of a pre-existing network and the overall cohesiveness of a pre-existing network, increased the efficiency of collaboration among Wikipedia contributors [16].…”
Section: Related Workmentioning
confidence: 99%
“…Many multiuser systems are complex by nature, involving agents in different roles, artifacts of different types, and complicated connections between agents, artifacts, and their environment. For example, work in Wikipedia occurs in 270 different languages and depends upon the contribution of tens of thousands of volunteer editors who take on a variety of tasks from creating new articles to writing policies (Bao et al, 2012 ;Welser et al, 2011 ). The editors are organized into hundreds of subgroups known as WikiProjects, and they collaborate on a technical infrastructure run by a nonprofi t organization.…”
Section: Step 2: Defi Ne Boundary Conditions and Build A Conceptual Mmentioning
confidence: 99%